Continuity or disruption? An assessment of changing work and employment in the Victorian construction industry. (3rd July 2017) - Veen, Alex; Teicher, Julian; Holland, Peter
ABSTRACT: This paper contributes to the literature on the changing nature of work and employment by focussing on the commercial and residential segments of the construction industry in one Australian state. Three key drivers of change in work and employment are identified and discussed: a changing competitive environment, technological advances in building methodologies and materials and a series of workforce-related issues. The findings are analysed through a theoretical lens which allows for a characterization of the nature, direction and extent of change in the industry. This combination allows for a characterization of the nature, direction and extent of change in the industry. Using interviews with key industry informants we identify and highlight reconfigurations of work and employment. A key finding of the study is that while technological advances are likely to give rise to some form of job destruction and deskilling, current developments are following an evolutionary rather than discontinuous trajectory of change.